Quality of Life After Treatment with Autologous Bone Marrow Derived Cells in No Option Severe Limb Ischemia. Issue 1 (January 2016) - Peeters Weem, S.M.O.; Teraa, M.; den Ruijter, H.M.; de Borst, G.J.; Verhaar, M.C.; Moll, F.L.
Abstract : Objective: Quality of life (QoL) is an important outcome in evaluating treatment effect in severe limb ischemia. The randomized, double blind, placebo controlled JUVENTAS trial, investigating the effect of bone marrow derived mononuclear cell (BMMNC) administration in no option severe limb ischemia, showed an improved QoL at 6 months compared with baseline in both the treatment and placebo groups. The aim of the present study was to evaluate whether the improved QoL persisted beyond 6 months' follow up, whether this differed in both trial arms, and if major amputation influenced QoL. Methods: Short form 36 (SF-36) and EuroQol 5D (EQ5D), including the EQ Visual Analogue Scale (EQ-VAS), questionnaires were sent to JUVENTAS trial participants. In the JUVENTAS trial, a norm based scoring method was applied to report the results of the SF-36. The results of the long-term follow up were compared with baseline and 6 month follow up and the results of both trial arms were compared, as were the results of patients with and without amputation. Results: One hundred and nine patients (86.5% of surviving patients) responded to the questionnaires. Median follow up after inclusion was 33 months (interquartile range [IQR] 21.2–50.6) for the BMMNC and 36 months (IQR 21.4–50.9) for the placebo group. The improvement in QoL at 6 months persisted in both arms at a median follow up of 35 months. The long-term QoL did not differ between the BMMNC and placebo group in any of the SF-36 or EQ5D domains. Patients with and without a major amputation had similar QoL scores. Conclusions: The increased QoL in patients with no option severe limb ischemia persisted until 3 years after inclusion, but did not differ between the BMMNC and placebo arms or between patients with and without a major amputation.